"Click-chemistry" inspired synthesis of hydrazone-based molecular glasses. Issue 11 (21st January 2016) - Magomedov, A.; Urnikaite, S.; Paliulis, O.; Jankauskas, V.; Getautis, V.
Abstract : Fast and simple synthesis of hole transporting materials inspired by "click-chemistry" was performed. Abstract : Fast and simple synthesis of hole transporting materials inspired by "click-chemistry" was performed. By employing hydrazone chromophores, high hole drift mobility (up to 0.0013 cm 2 V −1 s −1 ) and controllable morphology was achieved.